2021
DOI: 10.3389/fmed.2021.604694
|View full text |Cite
|
Sign up to set email alerts
|

A Simple-to-Use Web-Based Calculator for Survival Prediction in Acute Respiratory Distress Syndrome

Abstract: Background: The aim of this study was to construct and validate a simple-to-use model to predict the survival of patients with acute respiratory distress syndrome.Methods: A total of 197 patients with acute respiratory distress syndrome were selected from the Dryad Digital Repository. All eligible individuals were randomly stratified into the training set (n=133) and the validation set (n=64) as 2: 1 ratio. LASSO regression analysis was used to select the optimal predictors, and receiver operating characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…However, the complexity and extensive variables involved in the calculation process of Apache IV present challenges for timely and appropriate clinical decision-making. Liu Y et al's model is more parsimonious, but its AUC (0.75) is not as good as ours [19] . In a study by Gajic et al, a similar model exhibited comparable discriminatory ability but required organ function data at 3 days after intubation [20] .…”
Section: Discussioncontrasting
confidence: 64%
“…However, the complexity and extensive variables involved in the calculation process of Apache IV present challenges for timely and appropriate clinical decision-making. Liu Y et al's model is more parsimonious, but its AUC (0.75) is not as good as ours [19] . In a study by Gajic et al, a similar model exhibited comparable discriminatory ability but required organ function data at 3 days after intubation [20] .…”
Section: Discussioncontrasting
confidence: 64%
“…For example, the oxygenation index was not included in our analysis because only paucity data were available. In a most recent study, 56 the authors found that oxygenation index had low prognostic power (AUC 55.3%) for acute respiratory distress syndrome. Thirdly, the nomogram did not have specific markers for circulatory and renal failure.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the oxygenation index was not included in our analysis because only paucity data were available. In a most recent study [73], the authors found that oxygenation index had low prognostic power (AUC 55.3%) for acute respiratory distress syndrome. Secondly, the nomogram did not have speci c markers for circulatory and renal failure.…”
Section: Discussionmentioning
confidence: 98%